2007
DOI: 10.4141/a06-072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed texture, meal frequency and pre-slaughter fasting on behaviour, stomach content and carcass microbial quality in pigs

Abstract: L. 2007. Effect of feed texture, meal frequency and pre-slaughter fasting on behaviour, stomach content and carcass microbial quality in pigs. Can. J. Anim. Sci. 87: [479][480][481][482][483][484][485][486][487]. In this study, behaviour in lairage, weight and composition of stomach contents and carcass microbial contamination were studied in 96 barrows assigned to the following treatments: feed texture (FT; mash vs. pellets), meal frequency (MF; 2 vs. five meals per day) and fasting time (WT; 4, 14 and 24 h) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…In support of this hypothesis, Saucier et al, (2007) recently reported an interaction between feed type (pellets vs mash) and fasting time (4, 14, or 24 h) for full stomach, stomach water, and stomach solid weights. All weights decreased with increasing fasting time in pigs fed mash; however, in pigs fed pellets, full stomach and water content weights were less in pigs fasted 14 than 4 h, but greater after 24 h of fasting.…”
Section: Gastro-intestinal (Gi) Tract Characteristicsmentioning
confidence: 80%
See 4 more Smart Citations
“…In support of this hypothesis, Saucier et al, (2007) recently reported an interaction between feed type (pellets vs mash) and fasting time (4, 14, or 24 h) for full stomach, stomach water, and stomach solid weights. All weights decreased with increasing fasting time in pigs fed mash; however, in pigs fed pellets, full stomach and water content weights were less in pigs fasted 14 than 4 h, but greater after 24 h of fasting.…”
Section: Gastro-intestinal (Gi) Tract Characteristicsmentioning
confidence: 80%
“…Lower weights of full stomach and its contents have been reported in pigs fed ad libitum compared to those subjected to restricted feeding (Magras et al, 2000;Saucier et al, 2007). This difference can be explained by the intake of smaller feed portions at each meal in pigs with ad libitum access to feed, which favours food digestion and consequently accelerates stomach emptying (Laplace et al, 1981).…”
Section: Gastro-intestinal (Gi) Tract Characteristicsmentioning
confidence: 86%
See 3 more Smart Citations